Structural model of university social responsability - Ortiz-Paniagua, Carlos Francisco; Valencia, Joel Bonales; Esparza, Araceli Flores (Sustainability in Debate, 2021)
The study aims to analyze the University Social Responsibility (USR) policy implemented at the Michoacan State University (Universidad Michoacana de San Nicolás de Hidalgo - UMSNH) from the perspective of the university community. For that purpose, a Structural Equations Model in its variant of Partial Least Squares (PLS) was used from a theoretical/empirical construct on the USR. Five variables integrated into 17 indicators were used, obtained by a representative sample. The results are presented in two sections; a) USR performance at the UMSNH and; b) the role of each variable in the PLS model. It is concluded that the performance was regular and the Internal Management (IM) had a key impact on the model operation. In the management practice, this might help identify areas to improve the performance of this policy by sector and variables.